Psychometric Analysis of the Patient Health Questionnaire for Depression and Anxiety (PHQ-4) in Community Support Program Attendees in San Juan de Miraflores - Migone-Acosta, Leonardo (2025)
The adaptation of psychometric tests in the context of vulnerable populations in Lima Metropolitana is highly relevant due to its implications for diagnosis and assessment in mental health. This study aimed to identify the psychometric properties of the Patient Health Questionnaire for Depression and Anxiety (PHQ-4) in attendees of community support programs in San Juan de Miraflores. The sample consisted of 115 participants (M = 37.2 years, SD = 9.20; 89.6 % females and 10.4 % males). Exploratory factor analysis identified a unidimensional structure as the best-fitting internal model. The analysis yielded internal consistency coefficients above the minimum thresholds established for research contexts. The study also established percentile-based norms for vulnerable communities. The discussion outlines the implications for psychometric assessment and preventive diagnostics in these populations and proposes directions for future research.